Врахування взаємного впливу окремих мікросмужкових елементів на параметри антенних решіток - Prahlada, Rao K.; Vani, R. M.; Hunagund, P. V. (PE "Politekhperiodika", Book and Journal Publishers, 2019)
This article demonstrates the alleviation of mutual coupling of a simple and low-cost four-element microstrip array antenna by loading I-shaped slot-type electromagnetic band gap structure in the ground plane. FR-4 glass epoxy is used as dielectric substrate. Moreover, the proposed array antenna shows a better performance in terms of multi-band resonance. The antenna is resonating at four frequencies and a virtual size reduction of 78.48% is obtained. The designed array antenna possesses directional radiation properties. Mentor Graphics IE3D software is used to design and simulate the designed antennas and the measured results are obtained using vector network analyser.